Utilisation of internet resources for continuing professional development: a cross-sectional survey of general practitioners in Scotland. Issue 1 (December 2016) - MacWalter, Gordon; McKay, John; Bowie, Paul
Abstract Background Participation in continuing professional development (CPD) is a professional and regulatory expectation of general practitioners (GPs). Traditionally, CPD activity was undertaken face-to-face in educational settings, but internet based formats have found increasing favour. The need for doctors to use the internet for service and educational purposes is growing, particularly in support of specialty training and appraisal. We aimed to determine how GPs in Scotland utilise online resources in support of their CPD. This involved identifying which resources are used and how frequently, along with their preferences as to how and why they access these resources. Methods A cross sectional study was undertaken using an online questionnaire to survey general practitioners across Scotland. Data were subjected to descriptive analysis and differences in attitudinal responses between groups and Fischer's exact tests were calculated. Results Three hundred and eighty-three GP responses were received, with the majority being female (n = 232, 60.6 %) and GP partners (n = 236, 61.6 %). The majority used the internet on three or more working days per week or more frequently (n = 361, 94.3 %) with the three most common reasons being to obtain information for a patient (n = 358, 93.5 %), answering a clinical question (n = 357, 93.2 %) and CPD purposes (n = 308, 80.4 %). Of 37 online resources used by respondents, the top five were SIGN Guidelines (n = 303, 79.3 %), BMJ Learning (n = 279, 73.0 %), NICE Guidelines (n = 255, 66.8 %), GP Notebook (n = 243, 63.6 %) and Google (n = 234, 61.3 %). Low use of social media such as Facebook (n = 11, 2.9 %) and Twitter (n = 11, 2.9 %) was reported for CPD. A majority agreed that 'reading information online' (95.0 %) and 'completing online learning modules' (87.4 %) were the most valued online activities. Slow internet connections (n = 240, 62.7 %), website access restrictions (n = 177, 46.2 %) and difficulties logging into online CPD resources (n = 163, 42.6 %) were reported barriers. Significant response differences (P < 0.05) were found between groups based on high volume online usage, gender and age. Conclusions The majority of respondents had positive attitudes to using online resources for continuing professional development, and a preference for evidence-based and peer reviewed online resources. Information technology (IT) difficulties remain a barrier to effective utilisation. The findings have implications for future planning and design of online resources and IT infrastructure.